The use of environmental aspects in health economics on the example of the valuation of human life - Ewa Bandurska; Małgorzata Wojnarowska; Agnieszka Wojtecka; Marzena Zarzeczna-Baran (Economic and Environmental Studies (E&ES), 2014)
The aspects of environment's protection play double role in determining human's health- direct which was illustrated, by among others, Lalonde in his concept called the fields of health and indirect by being part of a methodology used in health economics. Improving quality of air, reducing its' pollution was the base of introducing the first study carried out in Poland in order to determine the value of non-market good, which is human's life. These calculations allowed to proceed the most universal pharmacoeconomic analysis - Cost Benefit Analysis (CBA). On the basis of Willingness To Pay (WPT) method, the VOLY indicator has been estimated within a range 40-70.000 PLN (the differences resulted from various assumptions in the methodology). Presently proceeded pharmacoeconomic methods do not use the aspects of environments' protection so commonly to assess the value of non-market goods, but it's important to remember that they were the most important elements of studies initiating the use of analysis of economic efficiency in Poland.
Keywords: 330; environment's protection; pharmacoecnomics; value of life; CBA analysis